Factors Influencing Chemotherapy-Induced Taste Alterations in Cancer Patients Receiving Cisplatin Treatment: A Path Analysis - Berna Kurt PhD; Berna Ömür Çakmak Öksüzoğlu MD (Cancer Control)
Introduction Cisplatin is particularly recognized for its adverse effects, most notably its impact on chemosensory perception. Methods This cross-sectional study enrolled 98 cancer patients undergoing cisplatin therapy from April 2022 to December 2023. Patients were administered the Chemotherapy-Induced Taste Alteration Scale (CITAS) and the Rhodes Index of Nausea, Vomiting, and Retching (RINVR). Results A multiple linear regression model was employed to determine the effect of taste changes among cancer patients undergoing cisplatin therapy. The study of the model coefficients for the structural model (χ 2 /df = 1.338, P = .004, GFI = 0.955, CFI = 0.986, RMSEA = 0.063, SRMR = 0.079) demonstrated a robust match. This model, formed to evaluate the effects of taste alteration, appetite loss, nausea, vomiting, age, quality of life, and body surface area, was statistically significant and explained 76.4% of the variation. Multiple linear regression evaluations determined significant factors affecting taste alteration associated with nausea-vomiting [(95% CI: 0.111-0.244); P =  0.042], loss of appetite [(95% CI: 0.102-0.254); P = 0.000], age [(95% CI: −0.827-0.424); P = 0.001], quality of life [(95% CI: −0.908-0.489); P = 0.000], and body surface area [(95% CI: 0.024-0.098); P = 0.021]. Conclusion Taste alteration significantly influenced symptoms of appetite loss, nausea, vomiting, age, and body surface area. These results provide valuable insights for developing effective intervention strategies to alleviate the relational effects of symptom clusters on patients’ quality of life and symptoms, particularly for cancer patients receiving cisplatin therapy.